Tourism potentials of Ulu Apad: a traditional governance system of the original Balinese people in Penglipuran Village - Anom Hery Suasapha (International Journal of Applied Sciences in Tourism and Events, 2022)
This paper aims to uncover the tourism potential of the Ulu Apad of Penglipuran Village. The Ulu Apad is a traditional governance system that exists only in a Bali Aga Village, believed to be the village of the original Balinese people. Using in-depth interviews and observation, the author extracted and discussed the tourism potentials of the Ulu Apad based on data collected from purposively selected informants. In addition, a literature review was carried out to provide secondary data. The result of the qualitative analysis shows that the Ulu Apad is a potential cultural tourist attraction. The system is so unique that it is different even from fellow Bali Aga Villages, and other customary villages. The system ensured that the most experienced and knowledgeable individuals are chosen to lead the village. Despite its uniqueness, the Ulu Apad has not been utilized as an attractor of tourist visits to the village due to its complexity. The intangible nature of the Ulu Apad means that special effort needs to be put in to ensure its attraction can be enjoyed by the tourist. This article provides insight into how to best utilize the intangible nature of the Ulu Apad as a cultural tourist attraction.